Glutathione S-transferase omega 2 regulates cell growth and the expression of E-cadherin via post-transcriptional down-regulation of β-catenin in human esophageal squamous cells. (18th November 2019) - Terayama, Masayoshi; Yamada, Kazuhiko; Hagiwara, Teruki; Inazuka, Fumika; Sezaki, Takuhito; Igari, Toru; Yokoi, Chizu; Nohara, Kyoko; Soma, Daisuke; Dohi, Taeko; Kawamura, Yuki I
Abstract: Glutathione S -transferase omega 2 (GSTO2), which belongs to the superfamily of GST omega class, lacks any appreciable GST activity. Although GSTO2 exhibits thioltransferase and glutathione dehydrogenase activities, its precise expression and physiological functions are still unclear. In the present study, we found that GSTO2 is exclusively expressed in the basal cell layer in Ki67-negative non-proliferative cells in the human esophageal mucosa. GSTO2 overexpression in esophageal squamous cell carcinoma (ESCC) cell lines inhibited cell growth and colony formation, and GSTO2-transfected cells formed smaller tumors in nude mice compared with mock-transfected cells. Interestingly, GSTO2 induction suppressed the expressions of E-cadherin and β-catenin at the cell–cell contact site. We quantified the phosphorylation levels of key proteins of MAPK signaling pathway and identified phosphorylation of p38. Additionally, HSP27, a downstream molecule of p38, was accelerated in GSTO2-transfected cells, unlike in mock-transfected cells. When GSTO2-transfected cells were treated with a p38 inhibitor, the expression of β-catenin and the membrane localization of E-cadherin was recovered. We next examined GSTO2 expression in 61 ESCC tissues using quantitative reverse transcription polymerase chain reaction and immunostaining. The results showed that GSTO2 mRNA and protein were significantly reduced in ESCC compared with normal tissues. When human ESCC cell lines were treated with 5-aza-2′-deoxycytidine, a DNA-methyltransferase inhibitor, GSTO2 transcription was induced, suggesting that aberrant hypermethylation is the cause of the down-regulated expression. Our results indicate that GSTO2 expression inhibits the membrane localization of E-cadherin, probably by modulation of the p38 signaling pathway. Down-regulation of GSTO2 by DNA hypermethylation contributes to the growth and progression of ESCC. Abstract : The present study first revealed that glutathione S -transferase omega 2 regulates cell growth and the expression of E-cadherin in esophageal epithelial cells, and it is a significant marker of esophageal stem/progenitor cells.